Prevalence of depression anxiety and stress in patients with osteoarthritis of knee - P. SATHYA; DRUSHA ZINGADE (International Journal of Pharma and Bio Sciences, 2019)
Knee osteoarthritis is a common degenerative joint condition and one of the most common causes of disability and pain in the elderly. Patients suffering from chronic painful disabling conditions frequently report anxiety and depression as co-morbidities. The objectives of the study were to find out: a) The prevalence of depression, stress and anxiety in OA knee patients. b) To compare which age group is affected more in females with osteoarthritis of knee c) To compare which age group is affected more in males with osteoarthritis of knee and d) To compare which gender with osteoarthritis of knee is affected more. A cross-sectional study was conducted among 76 patients suffering with osteoarthritis of knee to assess the level of depression, anxiety and stress using DASS-21(Depression Anxiety and Stress Scale-21). It was seen that females in the age group of 45-55 yrs with OA knee showed more anxiety and stress, while females in the age group of 55-65 yrs with OA knee showed more depression. Males in the age group of 55-65 yrs with OA knee showed more depression, anxiety and stress as compared to males in the age group of 45-55 yrs. This study also showed that prevalence of depression, anxiety and stress was seen more in females with OA knee than in males. Thus screening for symptoms of depression, anxiety and stress during the initial consultation is important because they are an indicator of poor prognosis. Because depression has clearly been shown to influence the clinical course of osteoarthritis, screening for depressive symptoms is crucial for optimal physiotherapy management.